PROVIDING COMPENSATION & REWARDS FOR GOOD PERFORMANCE - Ridwannudin, Muhammad; Sadat, Fahad Achmad (Politeknik Siber Cerdika Internasional, 2023)
In a company or organization, one of the most important elements is maintaining relationships between each other both between workers and to superiors, because a good work environment will bring performance to be more controllable and bring the work environment to be productive, this is what makes good performance in a company or organization. Several things can bring good performance as in this study which discusses Compensation and an Award to a worker for his performance which is classified as entering a good work stage so that efforts to provide compensation and awards make positive efforts and bring progress to the performance of workers in a company or organization and bring competence in the world of work. Compensation provided by the employer will bring workers to be more responsible in meeting work standards and the award is given as a reward for performance that has met operational standards for the company. The results of this study indicate that providing compensation and awards to a worker can bring positive value and can even improve the performance of these workers, where workers will become more enthusiastic in working and can even increase the value of the company, agency and even the organization where the worker works and the award shows that the worker has an achievement for good performance. Keywords: Compensation, Awards, Worker Performance.